FIQH DAN PERMASALAHAN PEREMPUAN KONTEMPORER - Muhammadun, Muzdalifah (LPPM IAIN Parepare, 2015)
The basic problem which is closely related to the women?s problems is the staying of patriarchal culture in contemporary society, which in a certain degree, it is in line with most of the cultural background of classical fiqh books. Meanwhile, the modernization has given the same opportunities for education between men and women, then gave a new awareness about their rights and obligations as a human being. When they tried to dismantle the shackles of bondage-cultural implications for women, in the same way, the gender biases in fiqh books will unfold. This paper attempts to uncover the contemporary women's issues in the perspective of jurisprudence, by opening the walls of women's fiqh which are gender biases.